Treatment of a schizophrenia patient on long-term super-dose antipsychotics: a case report - Xiaobo Xie; Jinzhang Chen; Hongli Song; Zebin Fan (Frontiers in Psychiatry)
IntroductionClozapine and chlorpromazine are widely used for treating schizophrenia. However, irregular medical follow-ups are common in patients with schizophrenia, potentially leading to long-term super-dose medication. Managing such cases poses significant challenges for clinical psychiatrists.Case presentationThis report describes a 24-year-old Han Chinese male diagnosed with schizophrenia who had been taking long-term super-doses of clozapine (18–107 tablets/day, 25 mg/tablet) and chlorpromazine (7–40 tablets/day, 50 mg/tablet) for five months due to irregular medical follow-ups. Upon hospitalization, the doses of antipsychotic drugs were gradually tapered, and the medication regimen was adjusted based on the patient’s previous treatment history. Comprehensive health education about schizophrenia was also provided. The patient was followed for four years, during which his psychiatric symptoms remained under partial control.ConclusionClinicians must consider individual differences in the efficacy and adverse effects of antipsychotics and weigh the benefits and risks of combination therapy. Future efforts should focus on strengthening health education for patients with schizophrenia and their families to improve treatment compliance and outcomes.